Exploring the application of multiple contradictory space elements and principles of M.C. Escher / Xidi Wang, Shaw Chiang Wong and Yuqian Zhang - Wang, Xidi; Chiang Wong, Shaw; Zhang, Yuqian (Faculty of Art and Design, 2024)
M.C. Escher, a renowned graphic artist, merged art and science to produce seemingly ‘unreasonable’ contradictory spaces that expand our vision into an infinite loop. Numerous designs have been influenced by his works. However, findings from the literature reveal that most adapt only a single contradictory space element or principle, while few explore more intriguing visual effects by incorporating multiple elements and principles. This study aims to explore the application of multiple Escher’s contradictory space elements through creative practice. A two-phase practice-based research approach was used. A graphic illustration was created in the first phase and was used as a stimulus in the second phase for semi-structured interviews with five conveniently selected individuals to assess their views on works integrating contradictory spatial elements and principles. The findings revealed contrasting opinions: while visitors found the work stimulating, triggering associations with the depicted subjects’ symbolic meanings and producing exciting spatial effects, they also perceived a lack of compositional order. While the creative practice and outcome could provide valuable references for other creative practitioners, the qualitative findings may inspire future research in related areas.